The effect of multiple role conflict and work stress on the performance of women nurses during the covid-19 with coping stress as intervening variables (Study at SoE Regional General Hospital) - Latunusa, Putri Margaret; Timuneno, Tarsisius; Fanggidae, Rolland E. (Goodwood Publishing, 2023)
Purpose: This study investigates the impact of multiple role conflict and work stress on the performance of married female nurses at SoE Regional General Hospital, with coping stress examined as an intervening variable. Research methodology: The sample in this study amounted to 35 respondents who were distributed to female nurses at SoE Hospital who were married. The data analysis method used is a quantitative analysis using a validity test, reliability test, classical assumption test, normality test, descriptive analysis, multiple linear analysis, t-test, and sobel test. Result: The results of the study using descriptive analysis using a range of scores are multiple role conflict variables are in the sufficient category, work stress, stress coping and performance are in a good category. The partial multiple-role conflict has a significant effect on performance, partial job stress has a significant effect on performance, Coping stress partially has a significant effect on performance, the effect of multiple role conflict on performance cannot be mediated by coping stress and the effect of work stress on performance can be mediated by coping stressed. Conclusions: The study concludes that role conflict undermines performance, but manageable work stress may enhance it when combined with effective coping strategies. Interventions that strengthen coping mechanisms are crucial in maintaining nurse performance during crises such as the COVID-19 pandemic. Limitations: The study’s findings are limited to one hospital and a small sample size, restricting generalization to broader contexts. Contribution: This research enriches organizational behavior literature by demonstrating the mediating role of coping stress and provides practical insights for hospital management in supporting nurses’ dual roles and stress management strategies.